PENGEMBANGAN PERANGKAT TES BAHASA ARAB BERBASIS KOMPETENSI UNTUK MADRASAH ALIYAH - YELFI DEWI (Ta'dib, 2013)
The aim of this research was to create Arabic test tool based on valid basic competency, practical and effective for Islamic Senior High School. The method of this research was research development. This research had three stages; front-end analysis, prototype, and assessment. Front-end analysis result showed that it was needed  an Arabic test tool as guidance to know the achievement of the teaching and learning objective. The Arabic test tool was designed based on the basic compentency. Then, the Arabic test tool was validated to the expert/ reviewer. The result of the research showed that: 1) Arabic test tool that was designed was already valid (content and construct validity) based on the expert and/or reviewer point of view; 2) The use of the Arabic test tool in teaching and learning process did not face any problems according to the students and teachers related to its practice; and 3) The Arabic test tool was already effective that can be seen from students’ opinion after getting test and their good mark. Kata kunci: bahasa Arab, pengembangan, perangkat tes, kompetensi